Construire des politiques alimentaires urbaines - Brand, Caroline; Bricas, Nicolas; Conaré, Damien; Daviron, Benoît; Debru, Julie; Michel, Laura; Soulard, Christophe Toussaint (2017)
This book describes the existing conceptual frameworks for an analysis of urban food policies at the crossroads of food system and sustainable city concepts. It serves as a basis to identify research issues in relation to local city government initiatives in the North and South.